Comparison of two methods for assessment of yield loss due to Turcicum leaf blight of maize - B. JAYARAMA GOWDA, H.S. PRAKASH and SANGAM LAL, K.T. PANDURANGE GOWDA, H. SHEKARA SHETTY (Indian Phytopathology, 2002)
Grain yield losses due to Turcicum leaf blight were assessed in two hybrids, Deccan and Ganga-S by two methods i.e., on the basis of whole TOWS and on the basis of varying disease levels. The results indicated that the method based on the average grain yield at different levels of infection is more reliable and authentic than the other based on whole TOW basis. The maximum grain loss was observed to be 4S.7 per cent on the rating of 5.0 on a scale of 1-5.